VIDEO COMPANY PROFILE AT CV. ZAKY SUKMA NURINDA - M Agung Pratama; Hendi Sama (ConCEPt - Conference on Community Engagement Project, 2022)
This writing focuses on making a company profile video at CV. Zaky Sukma Nurinda whose promotion is still using books and through clients who first come to the company so it is difficult to introduce the company to clients. The method used in making this company profile video is the first stage of pre-production, idea and concept design, script design, etc.; the production stage prepares the required production equipment and takes pictures. The last stages are post-production editing, rendering, and testing. The result of this is a company profile video at CV. Zaky Sukma Nurinda; and by making this video it is easier for CV. Zaky Sukma Nurinda introducing its company to clients.